Pengaruh Suku Bunga dan Pertumbuhan Ekonomi Terhadap Return Saham pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia - Wafa Mutmainah; Muhammad Iqbal Pribadi; Rahman Anshari (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study is to analyze the effect of interest rates and economic growth on stock returns in companies in the energy sector listed on the Indonesia Stock Exchange during the period 2019 to 2023. The method used is a quantitative approach with panel data regression analysis. The study population includes 90 company data from the sector. The sample was determined through a purposive sampling method, resulting in 46 companies that meet the established criteria. The results of the study indicate that interest rates have a significant effect on stock returns, while economic growth also shows a significant effect.